Calliini (Coleoptera, Cerambycidae, Lamiinae): descrições, homonímia, novo registro e chave para as espécies de Graminea Thomson, 1864 - Martins, Ubirajara R.; Galileo, Maria Helena M. (Papéis Avulsos de Zoologia, 2006)
Calliini (Coleoptera, Cerambycidae, Lamiinae): descriptions, homonym, new record and key to the species of Graminea Thomson,1864. New species described: Paracallia giesberti sp. nov. from Bolivia (Cochabamba), Colombicallia albofasciata sp. nov. and Graminea rubra sp. nov. from Bolivia (Santa Cruz); Asemolea flava sp. nov. from Costa Rica, (Heredia); Callia potiaiuba sp. nov. from Brazil (Rondônia) and Bolivia (Cochabamba and Santa Cruz). Rumuara nom. nov. is proposed for Paracladus Martins & Galileo, 1990 non Carpenter, 1966 (Orthoptera). Eumimesis trilineata Magno & Monné, 1990 is recorded for Bolivia. A key to the species of Graminea is added.